The effect of problem-based learning integrated individual rotation route on islamic character and critical thinking ability - Fendy Hardian Permana; Hajriani Hi.Padu; Rr Eko Susetyarini (Universitas Negeri Jakarta, 2022)
Entering the 21st century the quality of human resources is focused on critical thinking because they are able to compete in the era of globalization, which is developing so fast, as well as human resources who have good character. To improve critical thinking skills, the learning model must be active, innovative, and creative. This quantitative study aims to see the effect of the Individual Rotation Route learning model based on Problem Based Learning in improving students' critical thinking skills and Islamic character. The design of this study used a Quasi Experiment with Pre-test Post-tests Non-Equivalent Control Group design which involved 2 classes, each consisting of 20 students of class VII SMP Aisyiyah 3 Malang, Indonesia. Critical thinking ability is measured using critical thinking rubrics and Islamic character is measured using character success indicators. Collecting data using pre-test, post-test, assignment, and observation. In analyzing the data on students' critical thinking skills, the One-Way ANCOVA test and the One-Way ANOVA Islamic character test were used. The results of this study indicate that there is a significant change after being given the Individual Rotation Route learning model based on Problem Based Learning on students' critical thinking skills and has an effect on students' Islamic character because students are actively involved in the learning process.